Characterization of gut dominant microbiota in obese patients with nonalcoholic fatty liver disease - Li-ting Jin; Ming-Zhi Xu; Ming-Zhi Xu (Frontiers in Cellular and Infection Microbiology, 2023)
In obese patients, non-alcoholic fatty liver (NAFLD) is common. However, whether there is a connection between the gut microbiota and the onset of NAFLD in obese people is yet unknown. Using quantitative real-time PCR, the microbiota of feces of the eligible 181 obese individuals was identified to compare the differences in gut microbiota between obesity with NAFLD and simple obesity. According to the findings, the gut dominant microbiota was similar between obesity with NAFLD and simple obesity. Nonetheless, compared to the simple obesity group, the quantity of Faecalibacterium prausnitzii colonies was much lower in the obesity with the NAFLD group. Bacteroides were present in greater than 65% of both groups. Bacteroides, Clostridium leptum, and Clostridium butyricum accounted for more than 80% of the cases in the obesity with NAFLD group, whereas Bacteroides, Clostridium butyricum, and F. prausnitzii accounted for more than 80% of the cases in the simple obesity group. We look for potential contributing variables to obesity-related NAFLD and potential prevention measures for obese people. Based on a multi-factor logistic regression analysis, lymphocytes may be a risk factor for obesity with NAFLD while F. prausnitzii may be a protective factor. Additionally, F. prausnitzii is positively impacted by Bacteroides, Clostridium leptum, Clostridium butyricum, and Eubacterium rectale, yet adversely impacted by Enterobacteriaceae. Notably, lymphocytes and F. prausnitzii may help determine whether obese patients would develop NAFLD.